The Role of Transoral Robotic Surgery in the Management of Oropharyngeal Cancer: A Review of the Literature. (23rd April 2012) - Dowthwaite, Samuel A.; Franklin, Jason H.; Palma, David A.; Fung, Kevin; Yoo, John; Nichols, Anthony C.
Abstract : Background . Transoral robotic surgery (TORS) is an emerging treatment option for the treatment of head and neck malignancies, particularly for oropharyngeal squamous cell carcinoma (OPSCC). Preliminary studies have demonstrated excellent oncologic and functional outcomes that have led to a resurgence of interest in the primary surgical management of OPSCC. The aim of the present study was to review the evidence base supporting the use of TORS in OPSCC. Methods . Studies evaluating the application of TORS in the treatment of head and neck squamous cell carcinoma (HNSCC), and more specifically OPSCC, were identified for review. Further searches were made of reference lists for complete evaluation of minimally invasive surgery (MIS) in treating OPSCC. Results . Seventeen results relating to the application of TORS in treatment of OPSCC were identified. Further results relating to the role of transoral laser microsurgery (TLM) in OPSCC were included for review. Feasibility, oncologic, and functional data is summarized and discussed. Discussion . Management strategies for patients with OPSCC continue to evolve. Minimally invasive surgical techniques including TORS and TLM offer impressive functional and oncologic outcomes particularly for patients with early T-classification and low-volume regional metastatic disease. Potential exists for treatment deintensification, particularly in patients who are HPV positive.